THE EFFECT OF PROBLEM SOLVING METHOD ON READING PROFICIENCY OF 9TH GRADE STUDENTS OF MTSN TANJUNG PINANG - Ihsan Abyad, Muhammad; Annas, Al-Baihaqqi (Program Studi Pendidikan Bahasa Arab, 2025)
This study investigates the impact of applying the problem-solving approach on enhancing pupils' reading abilities. This study employs a quasi-experimental design and a quantitative methodology to ascertain its findings. A nonequivalent control group design is employed as the quasi-experimental design. Twenty-five students from class IX-1 and twenty-five students from class IX-3 participated in the study, which was carried out at Mtsn Tanjung Pinang. While students in class IX-3 received therapy using the problem-solving approach under the heading